Differences in Rubber Plant Production in Swamp and Land in North Sumatra - Rahmi Dwi Handayani Rambe; Mahyuddin Dalimunthe; Syamsafitri Syamsafitri; Indra Gunawan; Mhd. Nuh; Nurhayati Nurhayati (Postgraduate, University of Mataram, 2023)
This study aims to analyze the differences in the production of rubber planting in swamp land and land in North Sumatra. Rubber plants are one of the mainstay commodities in North Sumatra Province along with oil palm plantations. It's just that lately many rubber farmers are converting rubber land to oil palm land. This causes the production and price of rubber commodities to fluctuate. One way to prevent this is to plant rubber in swampy soil. This research uses descriptive qualitative research. Collecting data by observation, interviews, document analysis, literature study, especially using previous research data. The results of this study indicate that there has been a decline in rubber production during the last ten years due to the conversion of rubber land to oil palm land whose main consideration is economic motives, both the increasing price of palm oil and decreasing rubber prices. It's just that, at the same time, rubber plantations have started in swamps that were previously untouched. However, the results are not quite satisfactory compared to rubber plants in dry land. Further research is needed on the factors that influence it and solutions to these problems